Implementation of Electronic-Based Government System (SPBE) in Pegunungan Bintang District, Papua Pegunungan Province - Andre Patabang; Wirman Syafri; Layla Kurniawati (Sean Institute, 2025)
The implementation of the Electronic-Based Government System (SPBE) in the Pegunungan Bintang Regency Government, Papua Province, still faces various challenges that hinder the optimization of its implementation. This study aims to analyze, describe, and identify the dynamics of SPBE implementation, the inhibiting factors faced, and the strategies implemented by the Pegunungan Bintang Regency Government in overcoming these obstacles. This study uses a qualitative approach with a descriptive method. The sampling technique was carried out through purposive sampling and snowball sampling. Data were collected through observation, semi-structured interviews, and documentation studies. Data analysis was carried out with the stages of data reduction, data presentation, and drawing conclusions and verification to obtain comprehensive findings. The results of the study revealed that the implementation of SPBE in Pegunungan Bintang Regency has not run optimally when viewed based on the theory of Elements of Success in E-Government Implementation from the Harvard JFK School of Government. Several main inhibiting factors include limited quantity and quality of human resources, inefficient budget allocation to support digital transformation, and the absence of regional regulations that form the legal basis for SPBE implementation. To overcome these obstacles, the local government has taken strategic steps, such as compiling a periodic Workload Analysis (ABK), optimizing budget planning and management to support the implementation of SPBE, and strengthening cross-regional coordination in designing the SPBE architecture. In addition, the Communication and Informatics Office of Pegunungan Bintang Regency is also trying to compile a Standard Operating Procedure (SOP) to clarify the SPBE implementation mechanism at the local government level.